ANALISIS PENGEMBANGAN PARIWISATA DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN PULAU MOROTAI PROVINSI MALUKU UTARA - Adrianto S. Totona; Sampara Lukman; Ali Hanafiah Muhi (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
The purpose of this study is to analyze tourism development in increasing local revenue in Morotai Island Regency, to analyze the factors supporting and inhibiting tourism development in increasing local revenue in Morotai Island Regency, North Maluku Province and formulating tourism development strategies in increasing original income. area (PAD) in Morotai Island Regency, North Maluku Province. This study uses tourism theory according to Mill and Morrison with four components, namely market, travel, marketing and destinations with descriptive qualitative research methods. Sources of data used are primary data and secondary data. Data collection techniques with observation, interviews and documentation. Methods of data analysis with data reduction, data presentation, and drawing conclusions. The results of this study indicate that tourism development in increasing local revenue (PAD) of Morotai Island Regency is seen from four components, namely the market component. The facilities and infrastructure in question must be prepared by local governments, communities, communities and business actors in order to attract tourists to visit the location. tourist destinations in Morotai Island Regency that have not been touched by the Department of Tourism and Culture. The researcher's suggestions are to increase tourism development in four components, namely market, marketing, travel and destinations, then there are twelve suggestions for supporting and inhibiting factors and nine suggestions for tourism development strategies in increasing local revenue (PAD) of Marotai Island Regency.